A histone deacetylation inhibitor and mutant promote colony-type switching of the human pathogen Candida albicans. - Klar, A J (2001)
Most strains of Candida albicans undergo high frequency phenotypic switching. Strain WO-1 undergoes the white-opaque transition, which involves changes in colony and cellular morphology, gene expression, and virulence. We have hypothesized that the switch event involves heritable changes in chromatin structure. To test this hypothesis, we transiently exposed cells to the histone deacetylase inhibitor trichostatin-A (TSA). Treatment promoted a dramatic increase in the frequency of switching from white to opaque, but not opaque to white. Targeted deletion of HDA1, which encodes a deacetylase sensitive to TSA, had the same selective effect. These results support the model that the acetylation of histones plays a selective role in regulating the switching process.